Improved lipogenesis gene expression in liver is associated with elevated plasma angiotensin 1-7 after AT1 receptor blockade in insulin-resistant OLETF rats. (15th September 2022) - Godoy-Lugo, Jose A.; Mendez, Dora A.; Rodriguez, Ruben; Nishiyama, Akira; Nakano, Daisuke; Soñanez-Organis, Jose G.; Ortiz, Rudy M.
Abstract: Increased angiotensin II (Ang II) signaling contributes to insulin resistance and liver steatosis. In addition to ameliorating hypertension, angiotensin receptor blockers (ARBs) improve lipid metabolism and hepatic steatosis, which are impaired with metabolic syndrome (MetS). Chronic blockade of the Ang II receptor type 1 (AT1) increases plasma angiotensin 1-7 (Ang 1–7), which mediates mechanisms counterregulatory to AT1 signaling. Elevated plasma Ang 1–7 is associated with decreased plasma triacylglycerol (TAG), cholesterol, glucose, and insulin; however, the benefits of RAS modulation to prevent non-alcoholic fatty liver disease (NAFLD) are not fully investigated. To better address the relationships among chronic ARB treatment, plasma Ang 1–7, and hepatic steatosis, three groups of 10-week-old-rats were studied: (1) untreated lean Long Evans Tokushima Otsuka (LETO), (2) untreated Otsuka Long Evans Tokushima Fatty (OLETF), and (3) OLETF + ARB (ARB; 10 mg olmesartan/kg/d × 6 weeks). Following overnight fasting, rats underwent an acute glucose load to better understand the dynamic metabolic responses during hepatic steatosis and early MetS. Tissues were collected at baseline (pre-load; T0) and 1 and 2 h post-glucose load. AT1 blockade increased plasma Ang 1–7 and decreased liver lipids, which was associated with decreased fatty acid transporter 5 (FATP5) and fatty acid synthase (FASN) expression. AT1 blockade decreased liver glucose and increased glucokinase (GCK) expression. These results demonstrate that during MetS, overactivation of AT1 promotes hepatic lipid deposition that is stimulated by an acute glucose load and lipogenesis genes, suggesting that the chronic hyperglycemia associated with MetS contributes to fatty liver pathologies via an AT1-mediated mechanism. Graphical abstract: Image 1 Highlights: AT1 blockade increased basal circulating Ang 1–7, while the glucose challenge decreased it. AT1 blockade was associated with decreased expression of hepatic lipogenic genes during the glucose challenge. AT1 blockade decreases liver lipids and glucose, with further data suggesting improved hepatic glucose handling.